INTERNATIONAL CRIMINAL LAW ENFORCEMENT AGAINST CONFLICT IN YEMEN - Tantimin Tantimin (Legal Spirit, 2022)
War and conflict have always been human habits throughout the history of civilization. Starting from the beginning of the creation of humans on Earth, war has always been a determining factor for human survival, especially the establishment or destruction of civilizations in the world. Of the many conflicts that exist, the conflict in the form of rebellion attracts attention because it is between the ruling government and armed parties dissatisfied with the relevant government policies. The conflict in Yemen poses a threat to close neighboring countries, including Saudi Arabia. In March 2015, the Saudi Arabian government launched a military operation to crush the Houthi group and help to restore the legitimacy of the Yemeni government. However, this operation also cost the civilian population in Yemen. The United Nations Human Rights Council, through the Regional and International Expert Groups, responded by publishing a report stating that there were allegations of international crimes in the military operation. In order to answer the existing problems, a study based on the view of international criminal law is needed. Answering the urgency of this research, the type of legal-normative research is used with a statutory, conceptual, and analytical approach in reviewing this matter. The technique of tracing legal materials is document study.